Pengaruh Rasio-Rasio Keuangan Terhadap Kinerja Bank Di Indonesia (Studi Kasus pada Bank Pembangunan Daerah di Indonesia Periode 2008-2012) - Vivin Indarwati; Edy Anan (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2014)
This study aimed to examine the effect of Operating Expenses to Operating Income (ROA), Loan to Deposit Ratio (LDR), and Equity to Assets Ratio (EAR) on Return on Assets (ROA). The sampling technique used is proposive sampling criteria Regional Development Bank (BPD) in Indonesia, which presents the financial statements the period 2008-2012. The analysis technique used is multiple regression with least squares equation and hypothesis testing using t test to test the partial regression coefficient and F test to examine the mean effect together with the level of significance of 5%. It also performed classical assumption that include tests of normality, multicollinearity, heteroscedasticity test and autocorrelation test.Based on the classical assumption has been made that the variable is not found to deviate from the classical assumption. This shows the available data has been qualified using multiple linear regression model. The results of this study indicate that the variable ROA significant negative effect on ROA. LDR variable positive and significant impact on ROA. EAR variable positive and significant impact on ROA. Predictive ability of these three variables on ROA in the study by 75.9%, while the remaining 24.1% is influenced by other factors not included in the research model